Modeling and Simulation of Interfacial Turbulent Flows - E. Shirani (Journal of Applied Fluid Mechanics, 2011)
Majority of the fluid flows in nature and industries are turbulent flows. Due to their complexity, modeling and simulation of turbulent flows are still among the top research topics in the field of fluid mechanics. The objective of this work is to consider the turbulence effects at the interface. The presence of interface affects the turbulence structures and they become anisotropic near the interface. In this work, the main objective is to consider the fluctuations of the interface topology and their effects on the volume fraction and the surface tension force at the interface. These effects are important under some circumstances especially when the shape of the interface changes rapidly and abruptly. The surface tension forces and the volume fraction-velocity fluctuation correlation have also important impact on the interface topology and its complicated features such as coalescence and breakup. Different new models are presented and the impacts of those parameters on the flow at the interface are presented in this work. In developing the models for mean velocity-volume fraction fluctuations the inhomogeneity of the flow at the interface is taken into account. Both Reynolds Averaged Navier-Stokes Equations and the Large Eddy Simulation Techniques were used to simulate turbulent interfacial flows and implement the novel models introduced in this work. The Kelvin-Helmholtz instability, two-dimensional and three dimensional jets, and water/oil phase separation were simulated numerically and the results were compared with corresponding valid data and the accuracy of the models was examined.